Peer Actors and Theater Techniques Play Pivotal Roles in Improving Social Play and Anxiety for Children With Autism - Ioannou, Sara; Key, Alexandra P.; Muscatello, Rachael A.; Klemencic, Mark; Corbett, Blythe A. (Frontiers in Psychology, 2020)
Children with autism spectrum disorder (ASD) have significant difficulty in social functioning to include engaging in natural play with peers. Many children with ASD exhibit significantly less interactive play and more physiological stress during benign social encounters with same-age peers on a playground. Theatrical role-playing and performance with expert role models may provide a unique opportunity for children with ASD to learn to engage with other children in a safe, supportive environment. SENSE Theatre® is a peer-mediated, theatre-based program aimed at improving social competence in youth with ASD. Previous studies have shown significant improvements in social and communication skills following SENSE Theatre® intervention. The current project examined play with novel peers and self-reported anxiety before and after participation in SENSE Theatre®.. Participants included 77 children between 10-16 years with high-functioning (IQ>70) ASD. The combined sample of 3 cohorts was randomized to the experimental (EXP, N = 44) or waitlist control (WLC, N = 33) group. Participants in the EXP group received 40 hours (10, 4-hour sessions) of SENSE Theatre®. The Peer Interaction Paradigm, an ecologically-valid measure of natural play, was administered before and after the intervention. Group Play and Self Play on the playground equipment during solicited (T4) and unsolicited (T1) play were used in the current study. The State Trait Anxiety Scale for Children (STAIC; Spielberger, 1983) was used to measure self-reported current and persistent anxiety, respectively. Following treatment, children in the EXP group engaged in significantly more Group Play with novel peers F(2,73)=7.78, p = 0.007 and much less Self Play F(2, 73) = 6.70, p = 0.01 during solicited play compared to the WLC group. Regression analysis revealed that pre-treatment play and group status were significant predictors of solicited Group Play. Children in the EXP group reported significantly less Trait anxiety following intervention F(2,71) = 6.87, p = 0.01; however, State anxiety was comparable. Results corroborate previous findings of significant changes in social and play behavior in children with ASD following the peer-mediated, theatre-based intervention. Acting and theatrical performance with supportive role models facilitates social engagement in every-day settings with novel peers and reductions in self-reported anxiety